The neighbour's bull: Learning from animal breeding practices in Nicaragua - Ojango, Julie M.K. (International Livestock Research Institute, 2016)
In Nicaragua, cattle are kept for both meat and milk. Producers do not use artificial insemination much, and there is no dominant breed – most are a result of crosses. The researchers held a workshop with producers to better understand their breeding practices. While the farmers listed all the traits they thought important when selecting animals for breeding, during the practical exercise most did not keep to these criteria; they looked only at the animal’s colour or physiognomy. They said they used artificial insemination only when projects made it available. But during lunch, women who were preparing food asked about artificial insemination and its timing. That was when the team realized the important role of women in breeding practices and the need to train them. Interview with Julie Ojango (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684